Reputation: 7793
Ok so I have to prove the following sequent:
(p -> r) ^ (q -> r) |- p ^ q -> r
I understand why that is clearly correct and I also understand the rules of natural deduction. What I don't understand is how I go about proving it. Here is the model answer provided:
1. (p -> r) ^ (q -> r) |- p ^ q -> r premise
2. p ^ q assumption
3. p ^e 2
4. p -> r ^e 1
5. r ->e 4,3
6. p ^ q -> r ->i 2,5
(e = elimination / i = introduction).
Could someone provide me with a link or a 'dumbed-down' explanation? I feel like I am missing a simple concept that is causing this to be hard to understand... ?
For example, on line 4, why does it require the p from line 3 to remove the ->, where as in line 3, you can remove the ^ q without using a q?
I am sure this is quite straight forward but it doesn't seem to make sense to me... ?
Upvotes: 4
Views: 312
Reputation: 856
In line 2, you have p ^ q
which means that both p
and q
are true. From that follows that p
is true, because if both of them are true, then any single one is also true.
In line 4, r
is true only if p
is true. And in line 3 you have that p
is true. Therefore, r
is also true.
Upvotes: 4
Reputation: 10575
You can remove the ^ q without using q because p ^ q means p AND q -- p is true independent of q.
You can't remove the p -> without using p because p -> r means p IMPLIES r -- r is only guaranteed to be true if p is as well.
Upvotes: 0